Hubungan Lunges dan Step Up dengan Ketepatan Tendangan Mawashi Geri - Oktavian, Irfan Deny; Putra, Miftah Fariz Prima; CS, Ansar; Kardi, Ipa Sari; Yudistira, Indra; Indardi, Nanang (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is based on the issue of the mawashi geri kick technique, where athletes show a lack of aggression in the lunge movement, tiptoe during the step-up phase, or display asymmetrical foot posture. The purpose of this study is to examine the relationship between agility and dynamic balance with the accuracy of the mawashi geri kick, as well as the percentage contribution of each factor. This research uses a correlational method. The subjects of the study are female karate athletes from FORKI Wonogiri. Data collection was carried out using purposive sampling, with a population of 67 female karate athletes and a sample of 30 female athletes aged between 12–18 years. The research instruments used include the leg dynamometer test (to measure lunges), a 17 cm ladder for the step-up test, and a target accuracy test using a punching bag to evaluate the mawashi geri kick. The results of the study indicate a significant relationship between lunges and kick accuracy, with a contribution percentage of 58.33%. There is also a significant relationship between dynamic balance and kick accuracy with a contribution of 45%, as well as a combined relationship between lunges and step-ups with a percentage of 59% in influencing the accuracy of the mawashi geri kick in female FORKI Wonogiri athletes. The novelty of this study lies in identifying the relationship between lunges and step-ups in the physical testing and measurement of FORKI Wonogiri athletes, and proposing a structured series of lunge and step-up exercises to improve their physical performance.